2014
DOI: 10.1002/acn3.139
|View full text |Cite
|
Sign up to set email alerts
|

The influence of weather on migraine – are migraine attacks predictable?

Abstract: ObjectiveThe study aimed at elucidating a potential correlation between specific meteorological variables and the prevalence and intensity of migraine attacks as well as exploring a potential individual predictability of a migraine attack based on meteorological variables and their changes.MethodsAttack prevalence and intensity of 100 migraineurs were correlated with atmospheric pressure, relative air humidity, and ambient temperature in 4-h intervals over 12 consecutive months. For each correlation, meteorolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…Migraineurs are more sensitive to various environmental stimuli than individuals without migraine. However, only in some migraineurs a significant weather sensitivity could be observed . Recently, Scheidt et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migraineurs are more sensitive to various environmental stimuli than individuals without migraine. However, only in some migraineurs a significant weather sensitivity could be observed . Recently, Scheidt et al .…”
Section: Discussionmentioning
confidence: 99%
“…Migraineurs are more sensitive to various environmental stimuli than individuals without migraine. However, only in some migraineurs a significant weather sensitivity could be observed (15). Recently, Scheidt et al (30) reported that both increases and decreases in temperature led to an increase of migraine attack reports.…”
Section: E F F E C T S O F W E a T H E R O N T M D P A I N A N D M I mentioning
confidence: 99%
“…11 One cannot exclude the possibility of an attributional bias underlying the positive association of several characteristics. The uncertain generalizability of findings to primary care settings is one such limitation.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Former studies have shown a variable prevalence of seasonal variation of headache in migraineurs, depending on the study design and geographical location. 4,11 However, inter-subject differences contributing to seasonal sensitivity of migraineurs are not well evaluated. 4,11 However, inter-subject differences contributing to seasonal sensitivity of migraineurs are not well evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that patients were least likely to present on Sunday, with a peak in presentations on Thursday. Similarly, Hoffman et al [34] found a peak of migraine events mid-week, with the least number of events being on Sunday. Stress is the most commonly reported trigger factor for migraine.…”
Section: Triggers Affecting Arrival Time and Increased Arrivalsmentioning
confidence: 99%